Impacts of coronavirus on non-member RMG cactories in Bangladesh: a rapid survey jointly conducted by Brac University’s CED and JPGSPH - Rabbani, Atonu; Chowdhury, Fahim S. (Centre for Entrepreneurship Development (CED), Brac University, 2021)
This study, jointly undertaken by Mapped in Bangladesh (MiB) project of Centre for Entrepreneurship Development (CED) of Brac University and Brac James P Grant School of Public Health (JPGSPH) of BRAC University, is based on the survey on 555 export-oriented 3,342 factories from Dhaka, Gazipur, Narayanganj, and Chattogram districts, in Bangladesh. The factories were sampled from MiB’s database and contacted through phone calls. Addressing the context of the Covid-19 Pandemic period, findings from the survey suggest that the factories are gradually opening up which is depicted by the number of days they were operational, current employment status, current capacity utilization and orders in pipeline.